Optimization of Electric Field Assisted Mining Process Applied to Rare Earths in Soils - Pires, Carolina M. G. (2021)
The extraction of rare earths has been studied worldwide, however some of these processes have a high cost and can cause negative environmental impacts. In order to mine these species from the soil, Electric Field Assisted Mining arises as an alternative to conventional mining processes. Therefore, the experimental parameters can be improved to obtain better results in the extraction of these species. The aim of this paper is to propose the optimization of the Electric Field Assisted Mining process of yttrium, to obtain the optimal experimental configuration to be applied in real soils. An optimization problem was defined to obtain the maximum extraction mass of yttrium ion (Y3+), considering the limitation for the quantity of electric current density. A hybrid optimization technique was used, based on the sequential application of genetic algorithms and non-linear programming. Different optimal process configurations were obtained, considering distinct limits for the electric current density. The best experimental configuration resulted in 0.5386 V cm−1 electric field strength and 0.10 mol L−1 electrolyte concentration. This condition was reproduced in real soil, which obtained a Y3+ electromining efficiency of 41.48%. The results showed that this technique is promising for the extraction of rare earth in real soils.